2013
DOI: 10.1099/ijs.0.051532-0
|View full text |Cite
|
Sign up to set email alerts
|

Janibacter cremeus sp. nov., an actinobacterium isolated from sea sediment

Abstract: A novel Gram-stain-positive actinobacterium, designated HR08-44(T), was isolated from a sea-sediment sample collected from the foreshore of Rishiri Island, Japan, and its taxonomic position was investigated by a polyphasic approach. Phylogenetic analysis based on 16S rRNA gene sequence comparisons revealed that strain HR08-44(T) was closely related to the members of the genus Janibacter, with pairwise sequence similarities of 97.3-98.8 %. Strain HR08-44(T) had peptidoglycan type A1γ, with meso-diaminopimelic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…S2). The presence of DPG, PG and PI was consistent with analyses of other species of the genus Janibacter (Hamada et al , 2013; Martin et al , 1997; Yoon et al , 2000). The major fatty acids of strain 0704P10-1 T were iso-C 16 : 0 (47.21 %), C 17 : 1 ω8 c (12.45 %) and 10-methyl C 17 : 0 (10.43 %) (Table S1).…”
supporting
confidence: 84%
See 2 more Smart Citations
“…S2). The presence of DPG, PG and PI was consistent with analyses of other species of the genus Janibacter (Hamada et al , 2013; Martin et al , 1997; Yoon et al , 2000). The major fatty acids of strain 0704P10-1 T were iso-C 16 : 0 (47.21 %), C 17 : 1 ω8 c (12.45 %) and 10-methyl C 17 : 0 (10.43 %) (Table S1).…”
supporting
confidence: 84%
“…The genus Janibacter was originally proposed by Martin et al (1997) as a member of the family Intrasporangiaceae with the type species Janibacter limosus . At the time of writing, the genus comprises eight species with validly published names: Janibacter limosus (Martin et al , 1997), J. terrae (Yoon et al , 2000), J. melonis (Yoon et al , 2004), J. anophelis (Kämpfer et al , 2006), J. corallicola (Kageyama et al , 2007), J. hoylei (Shivaji et al , 2009), J. alkaliphilus (Li et al , 2012) and J. cremeus (Hamada et al , 2013). Janibacter brevis , originally described by Imamura et al (2000), has since been recognized as a heterotypic synonym of J. terrae (Lang et al , 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA profiles obtained allow discrimination at the subspecies level, based on the DNA diversity in the entire bacterial genome, offering a broad spectrum of genetic variation [ 17 , 40 ]. Sequencing results showed that most of the isolated strains were moderately halophilic bacteria growing optimally in media containing 3–10% (w/v) salt, as the species of Idiomarina , Psychrobacter [ 41 ], Kocuria [ 42 ] Staphylococcus , Virgibacillus [ 43 ] Planococcus [ 44 ] and Janibacter [ 45 ], and some species of the genera Bacillus . Interestingly, some strains were isolated only in media containing the highest NaCl concentrations (10–20% (w/v) NaCl), as those related to species of Halovibrio , Salicola , Marinococcus and some species of Bacillus [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, Janibacter could be divided into nine strain types: J. limosus, J. terrae, J. indicus, J. melonis, J. anophelis, J. hoylei, J. corallicola, J. alkaliphilus, and J. cremeus. [5][6][7][8][9][10][11][12][13] J. indicus was first isolated by Zhang et al in the Indian Ocean. The phylogenetic tree of J. indicus and other Janibacter strains was constructed by 16s rRNA, and revealed that J. indicus is related to J. terrae, J. cremeus, J. anophelis, J. hoylei, J. limosus, J. corallicola, J. melonis, and J. alkaliphilus (Zhang et al).…”
Section: Acknowledgmentmentioning
confidence: 99%